2008
DOI: 10.1212/01.wnl.0000318293.28278.33
|View full text |Cite
|
Sign up to set email alerts
|

Topiramate in pregnancy

Abstract: The number of outcomes of human pregnancies exposed to topiramate is low, but the major congenital malformation rate for topiramate polytherapy raises some concerns. Overall, the rate of oral clefts observed was 11 times the background rate. Although the present data provide new information, they should be interpreted with caution due to the sample size and wide confidence intervals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
155
1
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 260 publications
(173 citation statements)
references
References 15 publications
5
155
1
12
Order By: Relevance
“…MCM rates are reported as 4.2 % to 4.9 % for monotherapy use, with an increased risk of cleft lip and cleft palate and hypospadias [11,12]. The Australian pregnancy register reported a particularly high rate of MCMs for TPM when used as polytherapy, at 14.1 % with a relative risk of 4.32 (95 % CI 1.57-11.05) compared with no AED exposure [13].…”
Section: Tpmmentioning
confidence: 99%
“…MCM rates are reported as 4.2 % to 4.9 % for monotherapy use, with an increased risk of cleft lip and cleft palate and hypospadias [11,12]. The Australian pregnancy register reported a particularly high rate of MCMs for TPM when used as polytherapy, at 14.1 % with a relative risk of 4.32 (95 % CI 1.57-11.05) compared with no AED exposure [13].…”
Section: Tpmmentioning
confidence: 99%
“…While the mean birth weights were within normal limits; however, there was a clear trend toward lower birth weights amongst infants receiving TPM as part of AED polytherapy regimens, and in patients that received higher doses of TPM monotherapy. This observation has not yet been validated in other studies [Montouris et al, 2003;Hunt et al, 2008]. A more recent study also reported that TPM-exposed neonates presented a higher prevalence of low birth weight in non-malformed liveborn singletons (9.8%), than controls (3.6%), evidencing a RR of 2.7 (95%CI: 1.4-5.1).…”
Section: Topiramate (Topamax Topiragen)mentioning
confidence: 76%
“…However, side effects include nephrolithiasis and fetal deformities [13]. These factors limited its use in our patient.…”
Section: Discussionmentioning
confidence: 99%